The influence of accent and device usage on perceived credibility during interactions with voice-AI assistants - Pycha, Anne; Zellou, Georgia (Frontiers in Computer Science, 2024)
Voice-AI assistants offer innovative ways for people to interact with technology, such as delivering search results through human-sounding voices. Unlike printed text, however, voices are associated with particular characteristics, such as accents, which have the potential to influence perceived credibility. Voice-AI assistants are also a relatively new phenomenon, and while people who use them frequently may be inclined to trust them, other people may not be. The current study investigated how voice accent and frequency-of-use affected users' credibility assessments of search results delivered by voice-AI assistants. Participants, who were native speakers of American English and self-classified themselves according to how frequently they used voice-AI assistants, listened to statements produced by neural text-to-speech in either an American English or British English accent. They then rated the credibility of both the information content and the voice itself, along several dimensions. Results showed that in multiple conditions, participants perceived information delivered by British-accented voices as more credible than that delivered by American English-accented voices. Furthermore, frequencyof-use exerted a significant effect on perceived trustworthiness of a voice. These findings have implications for the ethical design of voice-AI systems, and for human-computer interaction more generally.